PENERAPAN METODE TARKIBIYYAH TAHLILIYAH DALAM PEMBELAJARAN QIRA’AH UNTUK MENINGKATKAN HASIL BELAJAR SISWA - Isop Syafe'i; Izzuddin Musthafa; Wirdah Hayati (Lahjah Arabiyah: Jurnal Bahasa Arab dan Pendidikan Bahasa Arab, 2020)
The purpose of this study are (1) to find out the learning outcomes of students at SDIT Atssurayya in qira’ah learning before using the tarkibiyyah tahliliyah method; (2) to find out the learning outcomes of students at SDIT Atssurayya in qira’ah learning after using the tarkibiyyah tahliliyah method; (3) to find out the increase in student learning outcomes in learning qira’ah. This research uses a quantitative approach and the method of quasi-experimental with a kind of one-group pretst and posttest design. The data collection techniques used were interviews, observation and tests. The results of this study note that student learning outcomes in learning qira’ah before the use of the tarkibiyyah tahliliyah method obtained an average yield of 69.31 and showed results that were not in accordance with the interpretation standards. And student learning outcomes after the use of the Tarkibiyyah tahliliyah method obtained an average result of 81.17 and showed good results in accordance with interpretation standards. Thus that the application of the method of tarkibyyah tahliliyah in learning qira’ah gives an increase in student learning outcomes with a percentage of 4% which shows the results that are in accordance with the criteria for the value of N-Gain.